2017
DOI: 10.1159/000456581
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis: Understanding the Dynamics of Bidirectional Wound Repair to Inform the Design of Markers and Therapies

Abstract: Background: Liver fibrosis is the final common pathway of iterative or chronic liver damage. When it reaches an advanced stage, cirrhosis develops and this indicates a loss of normal liver architecture, disruption of normal blood flow, the development of nodules of proliferative hepatocytes and consequent functional failure. Cirrhosis is also associated with life-threatening complications. Importantly, this dysregulation of blood flow involves changes resulting from both architectural disruption and a dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…The anti-fibrotic activity of RLX, previously showed in several organs, makes its potential effect in liver diseases worth exploring [3,6,8]. Treatment of fibrosis and its progression to cirrhosis is still an unmet need in the management of chronic liver diseases [23][24][25]. In this regard, we have investigated the efficacy of RLX in preventing the onset and progression of fibrosis in a mouse model of NASH, currently the most prevalent chronic liver disease [12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-fibrotic activity of RLX, previously showed in several organs, makes its potential effect in liver diseases worth exploring [3,6,8]. Treatment of fibrosis and its progression to cirrhosis is still an unmet need in the management of chronic liver diseases [23][24][25]. In this regard, we have investigated the efficacy of RLX in preventing the onset and progression of fibrosis in a mouse model of NASH, currently the most prevalent chronic liver disease [12][13].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are released into the extracellular environment where they contribute to collagen turnover. Their activity is finely regulated both at mRNA and at post-transcriptional level by the interaction with the tissue inhibitor of metalloproteinase proteins (TIMPs) 24 . After 96 hours, MMPs activity was significantly reduced in the cells treated with FFAs (p < 0.05 compared to CTRL).…”
Section: Determination Of Experimental Compound Concentration Survivmentioning
confidence: 99%
“…In addition, it has been demonstrated that the progression of liver fibrosis is reversible (11)(12)(13)(14). There are several therapeutic agents, including Orlistat, Metformin and Candesartan, typically used for anti-fibrotic therapy (15,16). However, the major limitation is the lack of effective treatment strategies for liver fibrosis (17,18).…”
Section: Introductionmentioning
confidence: 99%